The Civil-Military Gap Debates in Military Sociology - Mustafa Yücehan Akal; Adem Başpınar (İstanbul Üniversitesi Sosyoloji Dergisi)
This article draws attention to the dimensions of gap alongside the sources upon which the issue of civil-military gap is based, the theorizing dynamics following World War II, and the discussions that have come to the agenda within the scope of the subject. Civil-military gap emerged as a subject of civil-military relations in the United States during the Cold War, with the idea that a large and permanent standing army poses a threat to social values. This issue emerged in the search for the most appropriate military control model in favor of democracy and has been the focus of academic attention due to the changes in military service and the increase in tensions in civil-military relations.